Older women and lower self-rated health. - Tengku Abdul Hamid, Tengku Aizan; Momtaz, Yadollah Abolfathi; Syed Abdul Rashid, Sharifah Norazizan (Taylor & Francis Group, 2010)
Several studies have found that older women report lower self-rated health than men. However, it is not clear why older women are more likely to report poor self-rated health than older men. Data for this study came from a national cross-sectional survey, Mental Health and Quality of Life of Older Malaysians (MHQoLOM). Included in the survey were 2980 respondents consisting of Malaysians aged 60 years and over, with both men (n = 1428) and women (n = 1552) represented. Results of t-tests showed older men expressed significantly higher levels of self-rated health and self-esteem than women (p < .01). Separate multivariate regression by gender revealed that age, life-threatening problems, and self-esteem were highly significant predictors of self-rated health among older men and women and explained 18.4% of variance in self-rated health for men and 18.2% for women. In the last step we examined the main effects of gender on self-rated health using General Linear Models (GLM) Univariate by adjusting for age, life-threatening problems, and self-esteem. Results showed an insignificant difference in self-rated health between older men and women (F (1,2715) = 2.26, P = 0.13) only after adjusting for self-esteem. It can be concluded that self-esteem affects responses to self-rated health of older men and women.